Green synthesis of silver nanoparticles using latex extract of Euphorbia tirucalli: A novel approach for the management of root knot nematode, Meloidogyne incognita. (March 2019) - Kalaiselvi, D.; Mohankumar, A.; Shanmugam, G.; Nivitha, S.; Sundararaj, P.
Abstract: In recent years, research on novel nematicides has gained great interest to reduce world crop losses caused by plant parasitic nematodes. In this study, we explored the synthesis of silver nanoparticles (Et-AgNPs) by using latex extract of Euphorbia tirucalli against root-knot nematode species, Meloidogyne incognita . The physico-chemical properties of newly synthesized Et-AgNPs were determined using UV–Vis spectroscopy, Field Emission Scanning Electron Microscopy (FE-SEM), Fourier-Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD). The nematicidal activity of Et-AgNPs against second stage juveniles (J2) of M. incognita was tested based on in-vitro (mortality and hatching) and in-planta trials (infectivity and crop protection) at different concentrations. The findings indicated that Et-AgNPs were lethal to J2 and also inhibited egg hatching ( in-vitro ). In-planta trials suggest that infestation on tomato roots was significantly reduced when the Et-AgNPs were applied as a root dip treatment. Tomato plants treated with Et-AgNPs had healthier growth parameters with a concurrent reduction in overall gall formation, egg masses on roots, number of eggs per egg mass and J2 populations within the plants. From this study, it was concluded that Et-AgNPs are helpful for the management of M. incognita and will be an effective replacement for synthetic nematicides. Highlights: A green synthetic approach is proposed for silver nanoparticles (Et-AgNPs) using Euphorbia tirucalli latex extract. Synthesized Et-AgNPs were spherical and cubic in the size of 20–30 nm. Et-AgNPs showed nematicidal activity against Meloidogyne incognita in in-vitro and in-planta trials.